Effects of Prolonged Head-Down Bed Rest on Cardiac and Vascular Baroreceptor Modulation and Orthostatic Tolerance in Healthy Individuals - Barbic, Franca; Heusser, Karsten; Minonzio, Maura; Shiffer, Dana; Cairo, Beatrice; Tank, Jens; Jordan, Jens; Diedrich, André; Gauger, Peter; Zamuner, Roberto Antonio; Porta, Alberto; Furlan, Raffaello (Frontiers in Physiology, 2019)
Orthostatic intolerance commonly occurs after prolonged bed rest, thus, increasing the risk of syncope and falls. Baroreflex-mediated adjustments of heart rate and sympathetic vasomotor activity (muscle sympathetic nerve activity, MSNA) are crucial for orthostatic tolerance. We hypothesized that prolonged bed rest deconditioning alters overall baroreceptor functioning thereby reducing orthostatic tolerance in healthy volunteers. As part of the European Space Agency Medium-term Bed Rest protocol, 10 volunteers were studied before and after 21-days of -6º head down bed rest (HDBR). In both conditions, subjects underwent ECG, beat-by-beat blood pressure, respiratory activity and MSNA recordings while supine (REST) and during a 15-minute 80 head-up tilt (TILT) followed by a 3-minute –10 mmHg stepwise increase of lower body negative pressure to pre-syncope. Cardiac baroreflex sensitivity (cBRS) was obtained in the time (sequence method) and frequency domain (spectrum and cross-spectrum analyses of RR interval and systolic arterial pressure, SAP, variability). Baroreceptor modulation of sympathetic discharge activity to the vessels (sBRS) was estimated by the slope of the regression line between percentage of MSNA burst occurrence and diastolic pressure. Orthostatic tolerance significantly decreased after HDBR (12±0.6min) compared to before (21±0.6min). While supine, heart rate, SAP and cBRS were unchanged before and after HDBR, sBRS gain was slightly depressed after than before HDBR (sBRS: -6.0±1.1 versus -2.9±1.5 burst%*mmHg-1 respectively). During TILT, HR was higher after than before HDBR (116±4 b/min versus 100±4 b/min respectively), SAP was unmodified in both conditions, cBRS indexes were lower after HDBR (α index: 3.4±0.7 ms/mmHg; BRSSEQ 4.1±3.3) compared to before (α index: 6.4±1.0 ms/mmHg; BRSSEQ 6.8±3.7). sBRS gain was significantly more depressed after HDBR than before (sBRS: -4.4±0.4 versus -2.2±0.6 burst%*mmHg-1 respectively). Our findings suggest that baroreflex-mediated adjustments in heart rate and MSNA are impaired after prolonged bed rest. The mechanism likely contributes to the decrease in orthostatic tolerance.